A Historical Study of World Religious Monuments & Celebrities Memorable Places in Religious Perspective - Dr. Tayyaba Razzaq (jihat-ul-islam, 2023)
The most tangible expression of religious ecology is through the veneration of nature. Diversity of procedure & approaches were designated as holy in different religions, and they are held in deep respect in honour of their assumed holiness. Many examples can be seen through the glimpse into the human civilization & history. The sacred journey towards Religious Monuments & Celebrities Memorable Places is considered as a religious act suggested for the specific spiritual cause, and it stand for a corridor to scrupulous holy sites. This research study will explore the status of Pilgrimage and the holiness of sacred places in their particular religious doctrine and practice. The research study will elaborate that some sacred journeys are difficult and require great obligation to complete. The purpose of research is to examine the sacred places are a bond to their followers because they have heartily association with them. The devotees have to offer sacrifice and sometime keeps fasting and travel bare-footed. It is also persuaded by the world religions to visit these sacred monuments. People visit and purified spiritually. The qualitative methodology is adopted.